Green Synthesized Silver Nanoparticles: Antibacterial and Anticancer Activities, Biocompatibility, and Analyses of Surface-Attached Proteins - Wypij, Magdalena; Jędrzejewski, Tomasz; Trzcińska-Wencel, Joanna; Ostrowski, Maciej; Rai, Mahendra; Golińska, Patrycja (Frontiers in Microbiology, 2021)
Biosynthesis of AgNPs is regarded as a green, eco-friendly, low-priced process that provides small and biocompatible nanostructures with antimicrobial activity and potential application in medicine. The biocompatibility of these nanoparticles is related to the coating with biomolecules of natural origin. The synthesis of AgNPs was confirmed using UV-Vis, their morphology, crystalline structure, stability and coating were characterized using TEM, XRD, Zeta potential and FTIR. Antibacterial activity of AgNPs was evaluated by determination of MIC and MBC against E.coli, K.pneumoniae, P.aeruginosa, and S.aureus. The potential mechanism of antibacterial action of AgNPs was determined by measurement of ATP level. Since the use of AgNPs in biomedical applications depend on their safety, the in vitro cytotoxicity of AgNPs on MCF-7 human breast cancer cell line and murine macrophage cell line RAW 264.7 using MTT assay, cell LDH release and measurement of ROS level were assessed. The nanoparticle protein capping agent was identified using LC-MS/MS. Nanoparticles were spherical in shape, small in size (mean 13.2 nm), showed crystalline nature, good stability (-18.7mV) and presence of capping agents. They exhibited antibacterial activity (MIC=8-128 μg mL-1, MBC=64-256 μg mL-1) and significantly decreased ATP levels in bacterial cells after treatment with different concentrations of AgNPs. The in vitro analysis showed that the AgNPs demonstrated dose-dependent cytotoxicity against macrophages and cancer cells but higher against the latter than the former. Cell viability decrease was found to be 42.2-14.2% and 38.0-15.5% while LDH leakage 14.6-42.7% and 19.0-45.0%, respectively. IC50 values calculated for MTT assay was found to be 16.3 and 12.0 μg mL-1 and for LDH assay 102.3 and 76.2 μg mL-1, respectively. Moreover, MCF-7 cells released a greater amount of ROS than macrophages during stimulation with all tested concentrations of AgNPs (1.47-3.13 and 1.02-2.58 fold increase, respectively). The SDS-PAGE analysis revealed the presence of five protein bands at a molecular weight between 31.7 and 280.9 kDa. These proteins showed the highest homology to hypothetical proteins and porins from E. coli, Delftia sp. and Pseudomonas rhodesiae. Based on obtained results it can be concluded that biogenic AgNPs were capped with proteins and demonstrated potential as antimicrobial and anticancer agent.